Adrenalectomy for incidental and symptomatic phaeochromocytoma: retrospective multicentre study based on the Eurocrine® database. Issue 10 (16th July 2021) - Hallin Thompson, L; Makay, Ö; Brunaud, L; Raffaelli, M; Bergenfelz, A; ,
Abstract: Background: Phaeochromocytoma is sometimes not diagnosed before surgery and may present as an adrenal incidentaloma. The aim of this study was to investigate differences in clinical presentation and perioperative outcome in patients with subclinical and symptomatic phaeochromocytoma, and in patients operated with and without preoperative α-blockade. Methods: This was a retrospective observational study of patients with a histopathological diagnosis of phaeochromocytoma registered in Eurocrine®, the European registry for endocrine tumours, between 1 January 2015 and 31 March 2020. Patient characteristics, clinical presentation, tumour detection, and perioperative variables were analysed. Results: Some 551 patients were included. Of these, 486 patients (88.2 per cent) had a preoperative diagnosis of phaeochromocytoma. Tumours were detected as incidentalomas in 239 patients (43.4 per cent) and 265 (48.1 per cent) had a preoperative diagnosis of hypertension. Preoperative α-blockade was more frequently used in patients with a known phaeochromocytoma (350, 90.9 per cent) than in patients with other indications for adrenalectomy (16, 31 per cent). Complications did not differ between patients who had surgery because of catecholamine excess compared with those who had other indications for surgery (19 (3.9 per cent) versus 2 (3 per cent); P =  0.785), nor did the conversion rate from minimally invasive to open surgery differ between the groups. There were no obvious differences in complications, according to the Clavien–Dindo classification, based on preoperative α-blockade or not. Conclusion: Subclinical phaeochromocytoma detected incidentally is common. A significant proportion of patients with phaeochromocytoma did not have α-blockade before surgery, without an apparent effect on complications. Abstract : The aim of this study was to investigate differences in clinical presentation and perioperative outcome in patients with subclinical and symptomatic phaeochromocytoma. Patients from the European database, Eurocrine®, were included. The study showed that subclinical phaeochromocytoma is common. Members of the Eurocrine Council are co-authors of this study and are listed under the heading Collaborators. Lay Summary: Phaeochromocytoma is an unusual adrenal tumour with hormonal overproduction of catecholamines leading to a severe condition, including extreme hypertension in some situations. It is treated with surgery. Medical treatment before surgery is used to minimize surgical complications related to high blood pressure. A large proportion of phaeochromocytomas are detected incidentally, without symptoms, on radiological examination for other reasons. The aim of this study was to investigate differences in patient characteristics and surgical results in patients operated with or without symptoms of phaeochromocytoma. Patients registered in the large, European database, Eurocrine®, between 2015 and 2020 were included in the study. The study showed that phaeochromocytoma without symptoms is common. Medical treatment before surgery does not seem to affect complications.